2009
DOI: 10.1007/s00402-009-1014-6
|View full text |Cite
|
Sign up to set email alerts
|

War-related infected tibial nonunion with bone and soft-tissue loss treated with bone transport using the Ilizarov method

Abstract: The Ilizarov technique with bone transport continues to be the most versatile, adaptive and effective method of treatment in these complex cases, and can very successfully deal with the associated large soft-tissue and bony defects without the use of routine bone-grafting, systemic antibiotics or soft-tissue flaps.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
31
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(34 citation statements)
references
References 30 publications
2
31
0
1
Order By: Relevance
“…13 The most common complication, in accordance with previous studies, was pin tract infection which was seen in 8 (28%) of our patients, 5 (16%) had limb shortening, which healed on suitable parenteral antibiotics after culture and sensitivity. [14][15][16][17][18][19][20] Our study showed a good result in 80%, moderate in 17% and poor in 3% of patients which was comparable to the results of other series like Ajmera et al and Patil et al 21,22 The mean time for weight bearing was 6 months indicating that most of the fractures in the study united at an average period of 6 months. These results confirmed that LRS fixator provides immediate stability to fracture fragments and allows immediate weight bearing which ultimately promotes early fracture healing and reduced financial burden.…”
Section: Discussionsupporting
confidence: 85%
“…13 The most common complication, in accordance with previous studies, was pin tract infection which was seen in 8 (28%) of our patients, 5 (16%) had limb shortening, which healed on suitable parenteral antibiotics after culture and sensitivity. [14][15][16][17][18][19][20] Our study showed a good result in 80%, moderate in 17% and poor in 3% of patients which was comparable to the results of other series like Ajmera et al and Patil et al 21,22 The mean time for weight bearing was 6 months indicating that most of the fractures in the study united at an average period of 6 months. These results confirmed that LRS fixator provides immediate stability to fracture fragments and allows immediate weight bearing which ultimately promotes early fracture healing and reduced financial burden.…”
Section: Discussionsupporting
confidence: 85%
“…16 Similarly, Bumbasirević et al reported that soft tissue defects can be successfully closed by soft-tissue transport in majority of patients and by split-skin grafting in remaining patients. 20 Mckee et al reported single-stage osseous and soft tissue reconstruction using the Ilizarov method in patients with composite tissue defects. 21 We agree with Robert Rozbruch et al…”
Section: Discussionmentioning
confidence: 99%
“…Previous procedures in these patients included: axial external fixation (14), intramedullary nailing (1), ORIF (6), local debridement and vacuumassisted closure (VAC) therapy (14) and plastic surgery (8). Plastic surgery consisted of skin graft (5), soleus flap (2), and latissimus dorsi and serratus anterior transfer (1). Local infection was present in 14 of the 18 cases.…”
Section: Methodsmentioning
confidence: 99%
“…Wide resection of bone is frequently required during Ilizarov transport techniques [1,2,16,21], leaving the surgeon facing a difficult problem. The remaining gap reduces progressively during transport, but in the interim, the repair process is shifted from a normal biological fracture response to a process in which a fibrocartilaginous tissue caps the bone, mimicking nonunion.…”
Section: Introductionmentioning
confidence: 99%